Maternal supplementation with combined galactooligosaccharides and casein glycomacropeptides modulated microbial colonization and intestinal development of neonatal piglets. (November 2020) - Wu, Yujun; Zhang, Xiangyu; Tao, Shiyu; Pi, Yu; Han, Dandan; Ye, Hao; Feng, Cuiping; Zhao, Junying; Chen, Lijun; Wang, Junjun
Graphical abstract: Highlights: Dietary GC supplementation during only late gestation modulated microbiota of sows. Maternal GC supplementation shaped the microbial colonization of piglets. Maternal impacted microbiota contributed to better gut integrity and barrier of piglets. The modified intestinal barrier functions were associated with improved growth performance of piglets. Abstract: This study aimed to investigate the maternal effects of the combination (GC) of galactooligosaccharides (GOS) and casein glycomacropeptides (CGMP) on their offspring. Twenty-two multiparous sows were divided into CON group (basal diet) and GC group (basal diet plus GC, 10 g/d with a ratio of 2: 1). Our results indicated that GC supplementation elevated the litter's characteristics, faecal Prevotella, Fusobacterium and unclassified_f__Prevotellaceae of sows. Maternal GC supplementation also enriched norank_f__Ruminococcaceae, Christensenellaceae_R-7_group, Ruminococcaceae_UCG-005 and Ruminococcaceae_UCG-010, elevated their piglets' body weight on day 21 and enhanced intestinal barrier functions by upregulating mRNA transcript levels of tight junctions and mucins. Positive correlations of the enriched microbes and intestinal barrier parameters were found by the spearman correlation analysis. Collectively, maternal GC intervention modulated the neonatal microbiota colonization, which potentially promoted the gut development and growth performance of the piglets. Our findings will provide an insight for future application of GC in maternal-foetal nutrition.